University Spillovers and New Firm Location - David B. Audretsch; Erik E. Lehmann; Susanne Warning (Max Planck Institute for Research into Economic Systems, 2004)
This paper examines the impact of locational choice as a firm strategy to access knowledge spillovers from universities. Based on a large data set of young high-technology start-ups publicly listed in Germany, this study tests the propositions that geographic proximity to the university is shaped by different spillover mechanisms, research and human capital, and by different types of knowledge spillover, natural sciences and social sciences. The results suggest that spillover mechanisms as well as the type of spillovers are heterogeneous. Furthermore, it turns out that spillover effects are locally bounded.
Keywords: M13; R30; L20; 330; university spillover; new firm location; spillover mechanisms; Spillover-Effekt; Betriebliche Standortwahl; Unternehmensgründung; Hochtechnologiesektor; Forschungskooperation; Hochschule; Deutschland